Therapeutic roles of natural remedies in combating hereditary ataxia: A systematic review - Phang, Michael; Lew, Sze Yen; Chung, Ivy; Lim, William/W.K.; Lim, Lee Wei; Wong, Kah Hui (BMC, 2021)
Background Hereditary ataxia (HA) represents a group of genetically heterogeneous neurodegenerative diseases caused by dysfunction of the cerebellum or disruption of the connection between the cerebellum and other areas of the central nervous system. Phenotypic manifestation of HA includes unsteadiness of stance and gait, dysarthria, nystagmus, dysmetria and complaints of clumsiness. There are no specific treatments for HA. Management strategies provide supportive treatment to reduce symptoms.